Developing Intercultural Competence through Digital Storytelling: A Cross-Cultural Collaboration between Indonesian and Filipino EFL Students - Azizah, Siti; Setiawan, Slamet; Adi Nugroho, Himmawan (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This qualitative case study presents an effective pedagogical model for cultivating intercultural competence (ICC) and digital citizenship among Indonesian and Filipino English Foreign Language (EFL) students through cross-cultural collaboration. Despite the recognized effectiveness of Project-Based Learning (PBL), a gap exists in the literature that explicitly examines how PBL and digital platforms can simultaneously foster ICC through collaborative digital content creation among the distinct Southeast Asian student population. Investigating the collaborative process behind the creation of the digital story ‘One Sea, Two Cultures,’ the study reveals that digitally mediated PBL is a powerful method for achieving higher levels of ICC; the process facilitated a critical shift from basic cultural appreciation to a deeper understanding of shared maritime heritage, enhancing participant sensitivity, empathy, and openness. Furthermore, digital tools like Canva were instrumental in overcoming initial logistical and language barriers, while the project simultaneously provided an authentic context that effectively improved students’ EFL skills. This study, thus, validates the digital-based PBL approach as a credible pedagogical model for fostering responsible digital citizenship and robust cross-cultural communication in EFL instruction.